Numerical Study on the Thermal Hydraulic Characteristics in a Wire-Wrapped Assembly of LFRs - Li, Jun; Fang, Di; Guo, Chao; Wang, Mingjun; Deng, Jian; Tian, Wenxi; Qiu, Suizheng; Su, G. H. (Frontiers in Energy Research, 2020)
The concept of wire-wrapped assembly is always adopted in the liquid metal cooled reactor. The detailed 3-D thermal hydraulic behaviors of liquid metal in the wire-wrapped assembly are of great importance for the reactor’s core design and safety analysis. In the present work, the numerical study on the 19-pins wire-wrapped assembly cooled by lead-bismuth eutectic is carried out using CFD method. The geometrical model adopted in the current work is referred to the test section in KIT’s 19-pins experiments, which is a test assembly scaled based on the MYRRHA reactor. The established CFD model is validated against the benchmark initially. And results show that the SST k-ω model accompanying with the modified Prt is appropriate for the current problem. Then the numerical models are extensively used in the modelling of perturbed assembly flow with the cylindrical blockage. Also, the influences of blockage longitude, position and porosity on the thermal hydraulic characteristics in the assembly are evaluated. The local and global effects induced by various blockages are investigated in detail. This work is meaningful for the deep understanding of safety features under the condition of assembly blockage operation in LFR.